Marine biodiversity of an Eastern Tropical Pacific oceanic island, Isla del Coco, Costa Rica - Cortés, Jorge (Revista de Biología Tropical, 2012)
Isla del Coco (also known as Cocos Island) is an oceanic island in the Eastern Tropical Pacific; it is part of the largest national park of Costa Rica and a UNESCO World Heritage Site. The island has been visited since the 16th Century due to its abundance of freshwater and wood. Marine biodiversity studies of the island started in the late 19th Century, with an intense period of research in the 1930’s, and again from the mid 1990’s to the present. The information is scattered and, in some cases, in old publications that are difficult to access. Here I have compiled published records of the marine organisms of the island. At least 1688 species are recorded, with the gastropods (383 species), bony fishes (354 spp.) and crustaceans (at least 263 spp.) being the most species-rich groups; 45 species are endemic to Isla del Coco National Park (2.7% of the total). The number of species per kilometer of coastline and by square kilometer of seabed shallower than 200m deep are the highest recorded in the Eastern Tropical Pacific. Although the marine biodiversity of Isla del Coco is relatively well known, there are regions that need more exploration, for example, the south side, the pelagic environments, and deeper waters. Also, several groups of organisms, such as the flatworms, nematodes, nemerteans, and gelatinous zooplankton, have been observed around the Island but have been poorly studied or not at all. Citation: Cortés, J. 2012. Marine biodiversity of an Eastern Tropical Pacific oceanic island, Isla del Coco, Costa Rica. Rev. Biol. Trop. 60 (Suppl. 3): 131-185. Epub 2012 Dec 01